"Back off means stay with me". Perceptions of individuals with mild intellectual disability or borderline intellectual functioning about the group climate in a secure forensic setting. Issue 1 (1st February 2021) - Neimeijer, Elien; Kuipers, Judith; Peters-Scheffer, Nienke; Van der Helm, Peer; Didden, Robert
Abstract : Purpose: The purpose of this study is to provide an in-depth account of how individuelas with a mild intellectual disabilitiy or borderline intellectual functioning (MID-BIF; IQ 50–85) perceive their group climate in a secure forensic setting. Giving voice to these service users may provide relevant insights for secure forensic settings. Design/methodology/approach: The interpretative phenomenological analysis was used to explore what individuals with MID-BIF experience with regard to their group climate. Findings: In the interviews about the four domains of group climate (i.e. repression, support, growth and atmosphere), five overarching dimensions appeared, namely, autonomy, uniformity, recognition, competence and dignity. Depending on the person and the (treatment) context in which he/she resides, these five dimensions relate to all four factors of the group climate instrument. Originality/value: From the perspective of individuals with MID-BIF, this study contributes by providing a framework to "fine-tune" group climate on five dimensions. Training socio-therapists to be sensitive to interpret ambiguous signals on these dimensions can contribute to optimizing group climate in secure forensic settings.